Error Analysis and Simulation of Galerkin Spectral Approximation for Flow Optimal Control with State Constraint. (4th July 2018) - Li, Dingfang; Huang, Fenglin; Shi, Xiulian
ABSTRACT: We investigate the spectral approximation of optimal control governed by Stokes equations with integral state constraint. A good choice for basis functions leads the discrete system with sparse matrices. The optimality conditions are derived, a priori and a posteriori error estimates are presented in both H 1 and L 2 norms. Numerical experiment indicates the high precision can be achieved with the proposed method.